2007
DOI: 10.1126/science.1139522
|View full text |Cite
|
Sign up to set email alerts
|

TLR3 Deficiency in Patients with Herpes Simplex Encephalitis

Abstract: Some Toll and Toll-like receptors (TLRs) provide immunity to experimental infections in animal models, but their contribution to host defense in natural ecosystems is unknown. We report a dominant-negative TLR3 allele in otherwise healthy children with herpes simplex virus 1 (HSV-1) encephalitis. TLR3 is expressed in the central nervous system (CNS), where it is required to control HSV-1, which spreads from the epithelium to the CNS via cranial nerves. TLR3 is also expressed in epithelial and dendritic cells, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

41
962
1
10

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 1,000 publications
(1,026 citation statements)
references
References 38 publications
41
962
1
10
Order By: Relevance
“…However one study has reported that TLR3 is important in the human response 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 29 to HSV induced encephalitis (HSE). In this study it was found that two children with a heterozygous mutation in TLR3 were specifically predisposed to HSE [98].…”
Section: Tlrs and Herpes Simplex Encephalitismentioning
confidence: 67%
“…However one study has reported that TLR3 is important in the human response 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 29 to HSV induced encephalitis (HSE). In this study it was found that two children with a heterozygous mutation in TLR3 were specifically predisposed to HSE [98].…”
Section: Tlrs and Herpes Simplex Encephalitismentioning
confidence: 67%
“…IFNs contribute to host resistance to viral proliferation through activation of the Jak-Stat signaling pathway [27], and by triggering production of both RNAse enzymes that destroy cellular RNA (both host and viral) and double-stranded RNA-dependent protein kinase, which halts cellular translation [28]. Deficiencies in the immune response to HSV (e.g., defects in the TLR-3 pathway, including TLR3 itself, UNC93B1, TIR-domain-containing adapter-inducing IFN-β, tumor necrosis factor receptorassociated factor-3, TANK-binding kinase 1, or IFN regulatory factor-3) leave the host susceptible to HSVE [29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…associated with susceptibility to a variety of different pathogens. However, recently, several PID have been described that are characterized by an increased frequency of infections caused by selected pathogens such as mycobacteria, pneumococci [3] and herpes simplex virus [4,5]. Such "holes-in-the-repertoire" defects (for recent review see [6]) are likely to be common in the population and may, taken together, account for a substantial number of, hitherto largely undiagnosed, patients with PID.…”
Section: Introductionmentioning
confidence: 99%